Demonic grounds : black women and the cartographies of struggle - McKittrick, Katherine (University of Minnesota Press, 2006)
"Demonic Grounds moves between past and present, archives and fiction, theory and everyday, to focus on places negotiated by black women during and after the transatlantic slave trade. Specifically, Katherine McKittrick addresses the geographic implications of slave auction blocks, Harriet Jacobs's attic, black Canada and New France, as well as the conceptual spaces of feminism and Sylvia Wynter's philosophies." --Publisher's description.
Keywords: Women, Black -- America -- Social conditions.; African diaspora.; Human geography -- America.; Geography -- Psychological aspects.; Slavery -- America -- History.; Enslaved women -- America -- History.; Women, Black -- Political activity -- America.; Women, Black, in literature.; America -- Race relations.; America -- Geography -- Psychological aspects.; Femmes noires -- Amérique -- Conditions sociales.; Africains -- Pays étrangers.; Géographie -- Aspect psychologique.; Femmes esclaves -- Amérique -- Histoire.; Femmes noires -- Activité politique -- Amérique.; Noires dans la littérature.; Amérique -- Relations raciales.; Amérique -- Géographie -- Aspect psychologique.; SOCIAL SCIENCE -- Women's Studies.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; African diaspora; Geography -- Psychological aspects; Human geography; Race relations; Slavery; Women, Black, in literature; Women, Black -- Political activity; Women, Black -- Social conditions; Enslaved women; America; History